Curable resin composition and application thereof, honeycomb resin product and preparation method and application thereof

By using a curable resin composition to form a honeycomb resin product, the problem of insufficient compressive strength and flow conductivity of the proppant in the prior art is solved, and efficient oil and gas recovery and formation protection are achieved.

CN119264896APending Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311773025.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Propants in existing hydraulic fracturing technology cannot meet the high compressive strength and high flow conductivity at the same time, and are prone to deform under high temperature and high pressure conditions, resulting in low oil and gas reservoir mining efficiency and formation pollution.

Method used

Using a curable resin composition, including aqueous thermosetting resin, solvent-based thermosetting resin, emulsifier and curing agent, a honeycomb resin product is formed by modifying nano-silica and bisphenol phenolic resin as curing agents, and has high compressive strength. and low deformation rate, suitable for oil and gas reservoir mining.

Benefits of technology

Rapid curing under high temperature and high pressure conditions to form honeycomb proppants, improving oil and gas recovery, reducing formation pollution, and enhancing the flow diversion capacity of formation pores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264896A_ABST
    Figure CN119264896A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials and oil and gas exploitation, and discloses a curable resin composition and application thereof, a honeycomb-shaped resin product and a preparation method and application thereof. The curable resin composition comprises a component A and a component B, the component A and the component B independently exist; the component A comprises water-based thermosetting resin, solvent-based thermosetting resin, an emulsifier and water; the component B comprises a curing agent, and the curing agent is selected from modified nano silicon dioxide and / or bisphenol phenolic resin as shown in a formula I; # imgabs0 # A is a structural unit derived from an anhydride compound, and B is a structural unit derived from a polyamino compound; the bisphenol phenolic resin comprises a structural unit as shown in a formula II and a structural unit as shown in a formula III; based on the total weight of the bisphenol phenolic resin, the content of the structural unit shown in the formula II is 0-100 wt%, and the content of the structural unit shown in the formula III is 0-100 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials and oil and gas exploitation, and in particular to a curable resin composition and application thereof, a honeycomb resin product and a preparation method and application thereof. Background Art

[0002] The fracturing fluid system for shale gas reservoir exploitation is mainly water-based. Hydraulic fracturing technology mainly involves pumping fracturing fluid into the formation at a high rate to create cracks in the formation, and then injecting sand-carrying fluid with proppants to support the cracks and establish oil and gas transmission pathways. In response to a series of problems existing in conventional hydraulic fracturing technology, such as sand plugging, residue damage, equipment wear, and difficulty in effectively supporting the far end of the crack, scholars have conducted a lot of research on proppants, mainly by developing low-density proppants to meet the needs of enhancing the conductivity of the far end of the crack, and the basic requirement for proppants is that they can still maintain the original structural morphology under high pressure.

[0003] In the existing proppant-fracturing fluid system, in order to prevent proppant particles from settling, a high-viscosity fracturing fluid is usually required to suspend the particles. This fracturing fluid usually increases the viscosity of the fluid by adding a water-soluble polymer as a thickener. However, this fracturing operation requires special fluid preparation operations and equipment. At the same time, the pump power consumed when sending the high-viscosity fracturing fluid to a designated location underground and returning it is relatively large. In addition, the polymer compounds used in the fracturing fluid enter the formation along with the fracturing fluid. Some of the polymer compounds remaining underground will block the pores of the formation, resulting in a decrease in oil production and pollution of the formation. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems that the proppant in the prior art cannot simultaneously meet the requirements of high compressive strength and high conductivity, and is easy to deform under high temperature and high conditions, and to provide a curable resin composition and application, a honeycomb resin product and a preparation method and application thereof. Component A of the curable resin composition contains a water-based thermosetting resin and a solvent-based thermosetting resin, and is injected into the formation simultaneously with component B. It can be quickly cured to form a honeycomb proppant under high temperature and high pressure formation conditions, and can have both high compressive strength and low deformation rate.

[0005] In order to achieve the above object, the first aspect of the present invention provides a curable resin composition, wherein the curable resin composition comprises a water-based thermosetting resin, a solvent-based thermosetting resin, an emulsifier, a curing agent and water;

[0006] Wherein, the curing agent is selected from modified nano-silicon dioxide and / or bisphenol-formaldehyde resin as shown in Formula I;

[0007]

[0008] In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R 1 is an alkyl group having 1 to 4 carbon atoms;

[0009] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;

[0010] A is a structural unit derived from anhydride compounds, and B is a structural unit derived from polyamino compounds;

[0011] The bisphenol novolac resin comprises a structural unit shown in formula II and a structural unit shown in formula III;

[0012]

[0013] Among them, R 2 , R 3 Each independently is H, CH 3 CF 3 or CH 2 CH 3 ;

[0014] Based on the total weight of the bisphenol-formaldehyde resin, the content of the structural unit represented by formula II is 0-100wt%, and the content of the structural unit represented by formula III is 0-100wt%.

[0015] The second aspect of the present invention provides a honeycomb resin product, characterized in that it is made from the curable resin composition described in the first aspect of the present invention.

[0016] A third aspect of the present invention provides a method for preparing a honeycomb resin product, characterized in that the preparation method comprises:

[0017] The components in the curable resin composition described in the first aspect of the present invention are mixed and cured to obtain the honeycomb resin product.

[0018] The fourth aspect of the present invention provides a use of the curable resin composition described in the first aspect of the present invention or the honeycomb resin product described in the second aspect of the present invention in at least one of oil reservoir development, building floor tiles and adsorption materials.

[0019] Through the above technical scheme, the curable resin composition and application, honeycomb resin product and its preparation method and application provided by the present invention obtain the following beneficial effects: Component A in the curable resin composition contains water-based thermosetting resin, which has good fluidity. When it and component B are injected into a high-temperature and high-pressure formation environment respectively, the water-based thermosetting resin in the composition and a specific curing agent can be quickly cured to form a honeycomb product. The curing agent has a specific structure, and the product after reacting with the water-based thermosetting resin can be used as a proppant, and has both high compressive strength and low deformation rate. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] The first aspect of the present invention provides a curable resin composition, wherein the curable resin composition comprises component A and component B; wherein the component A and the component B exist independently;

[0022] The component A comprises a water-based thermosetting resin, a solvent-based thermosetting resin, an emulsifier, a curing agent and water;

[0023] The component B comprises a curing agent, and the curing agent is selected from the modified nano-silicon dioxide and / or bisphenol-formaldehyde resin shown in formula I;

[0024]

[0025] In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R 1 is an alkyl group having 1 to 4 carbon atoms;

[0026] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;

[0027] A is a structural unit derived from anhydride compounds, and B is a structural unit derived from polyamino compounds;

[0028] The bisphenol novolac resin comprises a structural unit shown in formula II and a structural unit shown in formula III;

[0029]

[0030] Among them, R 2 , R 3 Each independently is H, CH3 CF 3 or CH 2 CH 3 ;

[0031] Based on the total weight of the bisphenol-formaldehyde resin, the content of the structural unit represented by formula II is 0-100wt%, and the content of the structural unit represented by formula III is 0-100wt%.

[0032] In the present invention, the contents of the structural unit represented by formula II and the structural unit represented by formula III are not 0 at the same time, and the sum of the contents of the structural unit represented by formula II and the structural unit represented by formula III is 100%.

[0033] In the present invention, the curing agent is selected from the modified nano-silica and / or bisphenol-formaldehyde resin of the above structure, which can enable the water-based thermosetting resin and the solvent-based thermosetting resin to be fully cured when the curable resin composition is injected into a high-temperature and high-pressure formation, thereby forming a honeycomb resin product with a specific structure, high compressive strength and low deformation rate.

[0034] In a specific embodiment of the present invention, the modified nano-silica shown in Formula I is used as a curing agent. Since the modified nano-silica has a small particle size and a large specific surface area, it has good dispersibility in the epoxy resin and a high amino content. It presents a dendritic morphology on the surface of the nano-silica particles M. When it is added to the epoxy resin, it can undergo a bonding reaction with the epoxy groups in the epoxy resin, giving full play to the advantages of the two, so that the cured epoxy resin has a greater compressive strength.

[0035] In another specific embodiment of the present invention, the bisphenol phenolic resin is used as a curing agent. Since the bisphenol phenolic resin includes specific structural units I and II, the molecular chain of the bisphenol phenolic resin can be made to produce a micro-crosslinked structure, forming a phenolic resin with a micro-net, and finally the bisphenol phenolic resin has a special performance of ensuring that the cured resin product has a higher compressive strength under the condition of good water solubility. When it is used as a curing agent for curing epoxy resin, the high temperature resistance and compressive strength of the epoxy resin can be significantly improved. In particular, when the content of the structural unit shown in formula II and the structural unit shown in formula III in the bisphenol phenolic resin meets the above-mentioned specific content, due to the sulfonic acid group, the bisphenol phenolic resin has good water solubility and storage stability, and then further improves the compressive strength of the epoxy resin cured by it under high temperature and high pressure conditions.

[0036] According to the present invention, in Formula I, the acid anhydride compound is selected from at least one of maleic anhydride, phthalic anhydride and succinic anhydride.

[0037] According to the present invention, the polyamino compound has a linear polyethylene polyamino compound or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000, which is a structure shown in Formula IV:

[0038]

[0039] Here, p is an integer from 1 to 6.

[0040] In the present invention, the polyamino compound is selected from the above compounds, so that the amino content in the modified nano-silicon dioxide is high, and the curing effect of the water-based thermosetting resin and the solvent-based thermosetting resin is further improved.

[0041] According to the present invention, the particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g.

[0042] Furthermore, the particle size of the modified nano-silicon dioxide is 10-500nm, and the specific surface area is 50-500m 2 / g.

[0043] According to the present invention, the particle size dispersion coefficient of the modified nano-silicon dioxide is 0.09-0.15.

[0044] In the present invention, the particle size dispersion coefficient of the modified nano-silica satisfies the above range, which can improve the dispersibility of the modified nano-silica in water-based thermosetting resins and solvent-based thermosetting resins, and further improve the curing performance of the curable resin composition using the modified nano-silica as a curing agent.

[0045] According to the present invention, the amino content of the modified nano-silicon dioxide is 0.1-5 mmol / g.

[0046] According to the present invention, in the bisphenol-formaldehyde resin, Q is Among them, R 2 , R 3 Each independently is H or CH 3 .

[0047] Furthermore, R 2 , R 3 Each independently is CH 3 .

[0048] According to the present invention, based on the total weight of the bisphenol-formaldehyde resin, the content of the structural unit represented by formula II is 60-80 wt %, and the content of the structural unit represented by formula III is 20-40 wt %.

[0049] According to the present invention, the weight average molecular weight of the bisphenol novolac resin is 2000-10000 g / mol.

[0050] Furthermore, the weight average molecular weight of the bisphenol novolac resin is 3000-5000 g / mol.

[0051] According to the present invention, in the curable resin composition, the content of the aqueous thermosetting resin is 5-40 parts by weight, the content of the solvent-based thermosetting resin is 10-76 parts by weight, the content of the emulsifier is 0.5-4 parts by weight, and the content of water is 16-50 parts by weight.

[0052] In the present invention, in the curable resin composition, each component satisfies the above range, so that the composition can be rapidly cured in a high-temperature and high-pressure formation environment to form a honeycomb product.

[0053] Furthermore, in the curable resin composition, the content of the aqueous thermosetting resin is 30-40 parts by weight, the content of the solvent-based thermosetting resin is 20-40 parts by weight, the content of the emulsifier is 2-3 parts by weight, and the content of water is 17-48 parts by weight.

[0054] According to the present invention, relative to the total amount of component A, the amount of component B is 40-80 parts by weight, preferably 60-80 parts by weight.

[0055] According to the present invention, the water-based thermosetting resin has a structure shown in Formula V;

[0056]

[0057] R 4 is a C1-C3 alkylene group;

[0058] Ar Among them, R 5 , R 6 Each independently is H, CH 3 CF 3 or CH 2 CH 3 ;

[0059] 0 <y1+y2≤8;

[0060] M is K or Na.

[0061] In the present invention, the water-based thermosetting resin contains hydrophilic sulfonate groups, which can significantly improve the hydrophilicity of the water-based thermosetting resin. When it is mixed with a solvent-based thermosetting resin and a specific curing agent is added, a phase change reaction can occur under formation conditions to form a honeycomb solid phase proppant.

[0062] According to the present invention, R 4 It is a C1-C3 alkylene group.

[0063] According to the present invention, Ar is Among them, R 5 , R 6 Each independently is H, CH 3 CF 3 or CH 2 CH 3 .

[0064] According to the present invention, M is Na.

[0065] According to the present invention, the content of S element in the water-based thermosetting resin is 6-20wt%.

[0066] In the present invention, when the content of the S element in the water-based thermosetting resin meets the above range, the sulfonic acid group content in the water-based thermosetting resin meets the requirements, and thus the water-based thermosetting resin has excellent water solubility and can be stably dispersed in an aqueous solution.

[0067] Furthermore, the content of S element in the water-soluble thermosetting resin is 10-15wt%.

[0068] According to the present invention, the epoxy equivalent of the waterborne thermosetting resin is 100-300 g / eq.

[0069] In the present invention, the epoxy equivalent of the water-based thermosetting resin satisfies the above range, which can improve its reaction activity, so that the water-based thermosetting resin reacts more thoroughly during the curing reaction, further improves the compressive strength of the product prepared from the resin when used as a proppant, and is not easy to deform.

[0070] In the present invention, the epoxy equivalent test method is the hydrochloric acid-pyridine titration method.

[0071] Furthermore, the epoxy equivalent of the water-based thermosetting resin is 150-200 g / eq.

[0072] According to the present invention, the emulsifier is selected from cationic emulsifiers and / or anionic emulsifiers.

[0073] Further, the cationic emulsifier is selected from at least one of dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, behenyltrimethylammonium chloride, N,N-ethylenedioctadecyldimethylammonium chloride, dodecyldimethylbenzylammonium chloride, hexadecyldimethylbenzylammonium chloride and octadecyldimethylbenzylammonium chloride.

[0074] Furthermore, the anionic emulsifier is selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium oleate, sodium laurate, sodium rosin acid, sodium didodecylphenyl ether disulfonate, and sodium dibutylnaphthyl sulfonate.

[0075] According to the present invention, the solvent-based thermosetting resin is at least one selected from epoxy resin (EP), polyimide (PI) and unsaturated resin.

[0076] According to the present invention, at 25° C., the apparent viscosity of the curable resin composition is 100-400 mPa·s, preferably 200-300 mPa·s.

[0077] In the present invention, the apparent viscosity is the apparent viscosity within 30 minutes after the components A and B in the resin composition are mixed. This is because after 30 minutes, the component A will be cured due to the presence of the curing agent in the resin composition, and the apparent viscosity at this time will be meaningless.

[0078] The second aspect of the present invention provides a honeycomb resin product, characterized in that it is made from the curable resin composition described in the first aspect of the present invention.

[0079] According to the present invention, there are interconnected channels in the honeycomb resin product.

[0080] In the present invention, there are interconnected channels in the honeycomb resin product, which can support cracks and microcracks while making the cracks have excellent flow conductivity. When used in the oil reservoir field, the oil and gas recovery rate can be improved.

[0081] According to the present invention, the porosity of the honeycomb resin product is 1-40%.

[0082] According to the present invention, the pore size of the honeycomb resin product is 0.1-0.7 nm.

[0083] According to the present invention, the cell density of the honeycomb resin product is 200-10000.

[0084] According to the present invention, the density of the honeycomb resin product is 0.85-0.95 g / cm 3 .

[0085] In the present invention, the honeycomb resin product has the above-mentioned specific porosity, pore size, pore density and density, which enables the solid phase proppant to have high flow conductivity while still maintaining high compressive strength and low deformation degree.

[0086] In the present invention, the cell density refers to the number of cells within a certain size (1 cm×1 cm) of the honeycomb resin product.

[0087] Furthermore, the porosity of the honeycomb resin product is 20-30%.

[0088] Furthermore, the pore size of the honeycomb resin product is 0.3-0.5 nm.

[0089] Furthermore, the cell density of the honeycomb resin product is 1000-1500 cells / cm 2 .

[0090] Furthermore, the density of the honeycomb resin product is 0.88-0.91 g / cm 3 .

[0091] According to the present invention, the compressive strength of the honeycomb resin product is 20-40 MPa, preferably 30-40 MPa.

[0092] According to the present invention, at 40 MPa and 90° C., the deformation rate of the honeycomb resin product is less than or equal to 8%, preferably less than or equal to 4%.

[0093] A third aspect of the present invention provides a method for preparing a honeycomb resin product, characterized in that the preparation method comprises:

[0094] The components in component A of the curable resin composition described in the first aspect of the present invention are mixed, and then mixed with component B and cured to obtain the honeycomb resin product.

[0095] According to the present invention, the curing conditions include: a curing temperature of 90-150° C. and a curing time of 10 min-6 h.

[0096] Furthermore, the curing conditions include: curing temperature of 120-150° C. and curing time of 30 min-4 h.

[0097] In the present invention, there is no particular limitation on the mixing conditions of the components in component A and the mixing conditions of component A and component B, as long as the components can be fully mixed and uniform.

[0098] The fourth aspect of the present invention provides a use of the curable resin composition described in the first aspect of the present invention or the honeycomb resin product described in the second aspect of the present invention in at least one of oil reservoir development, building floor tiles and adsorption materials.

[0099] The present invention will be described in detail below by way of examples. In the following examples,

[0100] The porosity of honeycomb resin products is measured using saturated liquid volume.

[0101] The pore size of the honeycomb resin product is measured by stereo microscope observation, specifically:

[0102] The honeycomb resin product was observed under a stereo microscope, and the pore diameter of the honeycomb resin product was tested within a field of view of 1 cm×1 cm. The pore diameters of 20 holes were tested, and the average value was taken as the pore diameter of the honeycomb resin product.

[0103] The cell density of the honeycomb product is measured by a stereomicroscope statistical method, specifically:

[0104] The honeycomb resin product was observed under a stereo microscope, and the pore size of the honeycomb resin product was tested within a field of view of 1 cm×1 cm. The pore size of 20 holes was tested, and the average value was taken as the pore size D, mm, of the honeycomb resin product. The pore density was calculated by the following formula: pore density, pores = (1 cm×1 cm)×porosity / pore area, where the pore area was calculated based on the pore being a circular pore, that is, pore area = π×(D / 2) 2 , mm 2 .

[0105] The compressive strength of honeycomb resin products is measured using a universal weight loading machine.

[0106] The deformation rate of honeycomb resin products is measured according to the following method:

[0107] At normal pressure and 25°C, the diameter of the tested honeycomb resin product is D0. At 40MPa and 90°C, the honeycomb resin product is extruded using a high and low temperature universal material testing machine. The diameter of the tested honeycomb resin product after extrusion is D1. The deformation rate = (D0-D1) / D0×100%.

[0108] The density of the honeycomb resin product is measured by observation and statistics using a stereo microscope.

[0109] The apparent viscosity of the curable resin composition is measured using a six-speed rotational viscometer.

[0110] The weight average molecular weight of the aqueous thermosetting resin is measured by gel permeation chromatography (GPC).

[0111] The S content in waterborne thermosetting resin was measured by elemental analysis.

[0112] The epoxy equivalent of waterborne thermosetting resin is measured using hydrochloric acid-pyridine.

[0113] According to the formulation in Table 1, curable compositions A1-A9, D1-D3 were prepared.

[0114] Wherein, the water-based thermosetting resin is prepared by the following method:

[0115] S1. 57 g of bisphenol A, 0.02 g of ferric chloride and 75 g of concentrated sulfuric acid are contacted for sulfonation reaction at a reaction temperature of 130° C. for a reaction time of 3 h to obtain a sulfonated bisphenol compound BPAS-1; wherein the molar ratio of bisphenol A to concentrated sulfuric acid is 1:3, and the mass ratio of bisphenol A to ferric chloride is 1:0.00035.

[0116] S2. Dissolve 8 g of NaOH in deionized water, add 48 g of BPAS-1, and dropwise add 18 g of epichlorohydrin at 50°C for polycondensation reaction. The reaction temperature is 50°C and the reaction time is 3 h to obtain a water-based thermosetting resin, wherein the mass ratio of BPAS-1 to NaOH is 1:0.17.

[0117] The content of S element in the water-based thermosetting resin is 13.4 wt%, the epoxy equivalent is 182 g / eq, the weight average molecular weight is 3891 g / mol, and R 1 is a C1 alkylene group, R 2 is 1, R 3 is 1, M is Na.

[0118] The modified nano silicon dioxide M1-M2 is prepared according to the following method:

[0119] Preparation of Nano-Silica M1

[0120] S1. Preparation of aminopropyl functionalized nano-silica:

[0121] Weigh 2g of the average particle size of 30nm and the specific surface area of ​​200m 2 / g of nano-silica particles were dispersed in 100mL of anhydrous toluene, and then 0.2g of aminopropyltriethoxysilane was added. The mixture was refluxed and stirred at 150°C for 24 hours under nitrogen protection. After the reaction, the solid product was centrifuged to obtain the solid product. The solid product was repeatedly washed with acetone and dichloromethane for 3 times, and vacuum dried at 40°C for 12 hours to obtain aminopropyl-functionalized nano-silica.

[0122] S2. Preparation of carboxyl functionalized nano-silica:

[0123] Weigh 2 g of the aminopropyl-functionalized nano-silica prepared above, disperse it in 50 mL of xylene, add 0.2 g of maleic anhydride, reflux and stir at 160 ° C for 6 hours under nitrogen protection, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40 ° C for 12 hours to obtain carboxyl-functionalized nano-silica.

[0124] S3. Preparation of modified nano-silica:

[0125] Weigh 1 g of the carboxyl-functionalized nano-silica prepared above, disperse it in 50 mL of toluene, add 0.25 g of diisopropylcarbodiimide (DIC) and 0.06 g of 1,8-diazabicycloundec-7-ene (DBU), stir and activate at room temperature (25°C) for 1 hour, then add 4 g of polyethyleneimine (number average molecular weight of 1500), continue to react at room temperature for 12 hours, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40°C for 12 hours to obtain modified nano-silica M1 with formula I structure, wherein n is 0, m is 3, and x is 3.

[0126] The particle size of the modified nano-silicon dioxide M1 is 30 nm and the specific surface area is 300 m 2 / g, the amino content is 2mmol / g, and the dispersion coefficient PDI is 0.11.

[0127] Preparation of Nano-Silica M2

[0128] The preparation method of M1 was followed, except that the specific surface area of ​​the nano-silica particles was 100 m 2 / g, and in step S3, the amount of polyethyleneimine used is 0.4g; the particle size of the modified nano-silicon dioxide M2 ​​is 30nm, and the specific surface area is 230m 2 / g, the amino content is 0.1mmol / g, and the dispersion coefficient PDI is 0.13.

[0129] The bisphenol novolac resins F1-F2 were prepared according to the following method.

[0130] Preparation of Bisphenol-formaldehyde Resin F1

[0131] S1, 57g bisphenol A, 0.03g ferric chloride and 25g concentrated sulfuric acid (98wt%) were contacted for sulfonation reaction, the reaction temperature was 130°C, the reaction time was 4h, wherein the molar ratio of bisphenol A to concentrated sulfuric acid was 1:1, and the mass ratio of bisphenol A to ferric chloride was 1:0.0005. After purification, monosulfonated bisphenol A-monomer B1 was obtained;

[0132] S2, under stirring conditions, 60g of the second monomer A (bisphenol A) and 21 parts by weight of the monomer B1 (monosulfonated bisphenol compound S1) were mixed with 30g of the first monomer (polyformaldehyde) in deionized water, and NaOH was added to make n(OH) - The concentration of the first monomer is 2 mol / L, and the polymerization is carried out at 50° C. for 4 hours to obtain a bisphenol novolac resin F1, wherein the amount of the first monomer is 27 wt %, the amount of the second monomer is 73 wt %, and the weight average molecular weight is 3657 g / mol, based on the total weight of the monomers.

[0133] Preparation of Bisphenol-formaldehyde Resin F2

[0134] According to the method for preparing F1, the difference is that the paraformaldehyde is replaced by an equal mass of formaldehyde to prepare bisphenol novolac resin F2, wherein the amount of the first monomer is 27wt%, the amount of the second monomer is 73wt%, and the weight average molecular weight is 4089g / mol based on the total weight of the monomers.

[0135] Preparation of Bisphenol-formaldehyde Resin DF1

[0136] The bisphenol-formaldehyde resin was prepared according to the method of F1, except that NaOH was added to make n(OH) - The molecular weight is 4 mol / L and the weight average molecular weight is 1203 g / mol.

[0137] Table 1

[0138]

[0139] Table 1 (continued)

[0140]

[0141]

[0142] Examples 1-9

[0143] According to the formula of Table 1 and Table 1 (Continued), the components of component A in the curable resin compositions A1-A9 and D1-D3 are mixed, and then mixed with component B and cured, wherein the curing conditions are: curing temperature 130° C., curing time 30 min, to obtain the honeycomb resin products L1-L9 and DL1-DL3.

[0144] Comparative Examples 1-3

[0145] The method of Example 1 is followed, except that A1 is replaced by D1-D3, to prepare honeycomb resin products DL1-DL3.

[0146] Test Case

[0147] The properties of the honeycomb resin products prepared in the examples and comparative examples were tested, and the results are shown in Table 2.

[0148] Table 2

[0149]

[0150]

[0151] From the above results, it can be seen that Examples 1-9 achieve good technical effects, have suitable pore structures, and have a compressive strength of not less than 30 MPa, while the deformation rate is not higher than 2%.

[0152] Among them, preferred embodiments 1-4 achieve significantly better technical effects, wherein the compressive strength is not less than 40 MPa and the deformation rate is not higher than 1.5%.

[0153] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A curable resin composition, characterized in that The curable resin composition comprises component A and component B; wherein the component A and the component B exist independently of each other; The component A comprises a water-based thermosetting resin, a solvent-based thermosetting resin, an emulsifier and water; The component B comprises a curing agent, and the curing agent is selected from the modified nano-silicon dioxide and / or bisphenol-formaldehyde resin shown in formula I; In formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R1 is an alkyl group having 1-4 carbon atoms; n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3; A is a structural unit derived from anhydride compounds, and B is a structural unit derived from polyamino compounds; The bisphenol novolac resin comprises a structural unit shown in formula II and a structural unit shown in formula III; Q Wherein, R2 and R3 are each independently H, CH3, CF3 or CH2CH3; Based on the total weight of the bisphenol-formaldehyde resin, the content of the structural unit represented by formula II is 0-100wt%, and the content of the structural unit represented by formula III is 0-100wt%.

2. The curable resin composition according to claim 1, wherein In Formula I, the acid anhydride compound is selected from at least one of maleic anhydride, phthalic anhydride and succinic anhydride; Preferably, the polyamino compound has a linear polyethylene polyamino compound having a structure shown in Formula IV or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000: Here, p is an integer from 1 to 6.

3. The curable resin composition according to claim 1 or 2, wherein The particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g; Preferably, the particle size of the modified nano-silicon dioxide is 10-500nm and the specific surface area is 50-500m 2 / g; Preferably, the particle size dispersion coefficient of the modified nano-silicon dioxide is 0.09-0.15; Preferably, the amino content of the modified nano-silica is 0.1-5 mmol / g.

4. The curable resin composition according to any one of claims 1 to 3, wherein Q is Wherein, R2 and R3 are each independently H or CH3, preferably CH3; Preferably, based on the total weight of the bisphenol-formaldehyde resin, the content of the structural unit represented by formula II is 60-80wt%, and the content of the structural unit represented by formula III is 20-40wt%.

5. The curable resin composition according to any one of claims 1 to 4, wherein The weight average molecular weight of the bisphenol novolac resin is 2000-10000 g / mol, preferably 3000-5000 g / mol.

6. The curable resin composition according to any one of claims 1 to 5, wherein In the component A, the content of the aqueous thermosetting resin is 5-40 parts by weight, preferably 30-40 parts by weight, the content of the solvent-based thermosetting resin is 10-76 parts by weight, preferably 20-40 parts by weight, the content of the emulsifier is 0.5-4 parts by weight, preferably 2-3 parts by weight, and the content of water is 16-50 parts by weight, preferably 17-48 parts by weight; Preferably, the mass ratio of the modified nano-silicon dioxide to the bisphenol-formaldehyde resin is 1:10-20, preferably 1:12-15; Preferably, relative to the total amount of component A, the amount of component B is 40-80 parts by weight, preferably 60-80 parts by weight.

7. The curable resin composition according to any one of claims 1 to 6, wherein The water-based thermosetting resin has a structure shown in Formula V; R4 is a C1-C3 alkylene group; Ar Wherein, R5 and R6 are each independently H, CH3, CF3 or CH2CH3; 0 <y1+y2≤8; M is K or Na.

8. The curable resin composition according to claim 7, wherein R4 is a C1-C2 alkylene group; Preferably, Ar is Wherein, R5 and R6 are each independently H, CH3, CF3 or CH2CH3; M is Na.

9. The curable resin composition according to any one of claims 1 to 8, wherein The content of S element in the water-soluble thermosetting resin is 6-20wt%, preferably 10-15wt%; Preferably, the epoxy equivalent of the waterborne thermosetting resin is 100-300 g / eq, preferably 150-200 g / eq.

10. The curable resin composition according to any one of claims 1 to 9, wherein The emulsifier is selected from cationic emulsifiers and / or anionic emulsifiers; Preferably, the cationic emulsifier is at least one selected from the group consisting of dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, behenyltrimethylammonium chloride, N,N-ethylenedioctadecyldimethylammonium chloride, dodecyldimethylbenzylammonium chloride, hexadecyldimethylbenzylammonium chloride and octadecyldimethylbenzylammonium chloride; Preferably, the anionic emulsifier is selected from at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium oleate, sodium laurate, sodium rosin acid, sodium didodecylphenyl ether disulfonate, and sodium dibutylnaphthyl sulfonate.

11. The curable resin composition according to any one of claims 1 to 10, wherein The solvent-based thermosetting resin is selected from at least one of epoxy resin, polyimide, and unsaturated resin.

12. The curable resin composition according to any one of claims 1 to 11, wherein At 25° C., the apparent viscosity of the curable resin composition is 100-400 mPa·s, preferably 200-300 mPa·s.

13. A honeycomb resin product, characterized in that: Prepared from the curable resin composition according to any one of claims 1 to 12.

14. The honeycomb resin product according to claim 13, wherein interconnected channels exist in the honeycomb resin product.

15. The honeycomb resin product according to claim 13 or 14, wherein: The porosity of the honeycomb resin product is 1-40%, preferably 20-30%; Preferably, the pore size of the honeycomb resin product is 0.1-0.7 mm; preferably 0.3-0.5 mm; Preferably, the cell density of the honeycomb resin product is 20-450 cells / cm 2 , preferably 100-400 pcs / cm 2 .

16. The honeycomb resin product according to any one of claims 13 to 15, wherein: The density of the honeycomb resin product is 0.85-0.95 g / cm 3 , preferably 0.88-0.91 g / cm 3 .

17. The honeycomb resin product according to any one of claims 13 to 16, wherein: The compressive strength of the honeycomb resin product is 20-40 MPa; preferably 30-40 MPa; Preferably, at 40 MPa and 90° C., the deformation rate of the honeycomb resin product is less than or equal to 8%, preferably less than or equal to 4%.

18. A method for preparing a honeycomb resin product, characterized in that: The preparation method comprises: The honeycomb resin product is obtained by mixing the components in component A of the curable resin composition according to any one of claims 1 to 12, and then mixing and curing with component B.

19. The preparation method according to claim 18, wherein: The curing conditions include: curing temperature of 90-150°C and curing time of 10min-6h; Preferably, the curing conditions include: curing temperature of 120-150° C., and curing time of 30 min-4 h.

20. Use of the curable resin composition according to any one of claims 1 to 12 or the honeycomb resin product according to any one of claims 13 to 16 in at least one of oil reservoir development, building floor tiles and adsorbent materials.

Citation Information

Cited By

  • Curable resin composition and use thereof, and honeycomb resin product and preparation method therefor and use thereof

    EP4831261A1